Evaluation and application of electroanalysis for the determination of antioxidants - Ragubeer, Nasheen (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
The role of antioxidants in the prevention of neurodegenerative diseases has been well documented. The use of synthetic antioxidants has decreased due to the ssociation of these compounds with certain cancers. Thus, the search for novel natural antioxidants has gained much focus in research. Most common methods of determining antioxidant capacity are the radical generated assays and biological assays such as lipid peroxidation and the nitroblue tetrazolium assay. Electrochemical methods have been proposed for the determination of bio-active compounds such as antioxidants. The electrochemical methods of cyclic voltammetry and square wave voltammetry were evaluated for the determination of antioxidant capacity initially examining known antioxidants and then using plant extracts of Sutherlandia frutescens as a case study. The antioxidant properties determined by electrochemical methods were validated utilising the non-biological methods of the DPPH, TEAC, ferrozine and FC assay and biological pharmacological methods. The results indicated that Sutherlandia frutescens contains potent antioxidant compounds that are able to reduce lipid peroxidation. The electrochemical techniques of square wave voltammetry and cyclic voltammetry were applied for the screening of a large number of extracts of various algae for the detection of antioxidant compounds. The results indicated that electrochemistry can be used as a preliminary method for the rapid screening of a large number of crude samples for antioxidant compounds. Electrochemical methods were also evaluated as a method for guiding the isolation and purification of antioxidant metabolites in Sargassum elegans. Solvent partitioning and fractionation of the marine alga allowed for the purification of antioxidant compounds. At each step of purification electrochemical methods were utilized to determine which fractions contained the more potent antioxidant compounds and thus guide further purification. The purified antioxidant compounds were elucidated using NMR to determine the structure of the antioxidant compounds.
Keywords: Antioxidants; Nervous system -- Degeneration; Electrochemical analysis; Marine algae; Natural products; Marine metabolites; Sargassum; Legumes; Nuclear magnetic resonance